Microstructure Change of Nanosilica-Cement Composites Partially Exposed to Sulfate Attack - Huang, Qian; Zhao, Liang; Zhao, Chenggong; Liu, Dongsheng; Wang, Chaoqiang (International journal of concrete structures and materials, 2020)
The deterioration of cement composites containing nanosilica partially exposed to sulfate attack was studied, and the microstructure change of the composites was analysed by a scanning electron microscope (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD). The results showed that nanosilica–cement composites had better sulfate resistance compared to plain cement composite under partial exposure to sulfate attack, and their sulfate resistance increased as the nanosilica content increased (in the range of 0 to 5 wt% replacing cement by weight). The main sulfate products were gypsum and ettringite within the surface and inner parts, respectively in both the immersed and evaporation portions of the nanosilica–cement composites, which was consistent with the plain cement composite. Thus, the incorporation of nanosilica did not change the distribution characteristics of the sulfate products within the composites partially exposed to sulfate attack. However, the addition of nanosilica reduced the amount of sulfate products in both the immersed and evaporation portions, and their amount decreased with the increase of nanosilica content. The evaporation portions of the composites suffered chemical sulfate attack rather than sulfate salt crystallization. Nanosilica–cement composites could be applied in real partial exposure environments containing sulfate ions.